PENGARUH PRODUK, PROMOSI, HARGA, LOKASI TERHADAP MINAT BERKUNJUNG KEMBALI KE RAHMAT INTERNATIONAL WILDLIFE MUSEUM & GALLERY MEDAN - puja areyouda pandiangan; liasta ginting (Jurnal Media Informasi Manajemen, 2013)
The purpose of this research is to investigate and analyze the influence of product, promotion, price and location of the intention to visit again and determine the most dominant factor affecting intention to visit again.This study is associative by using a questionnaire distributed to visitors who have visited at least twice. The population in this study are all visitors in June 2011, which amounted to 3850 visitors. The sample size was determined using the Slovin formula samples in this study were respondents or 97.46 can be rounded to 97 people responden.Pengujian hypothesis using linear regression analysis.Based on calculations and data analysis has been done, the variable product, promotion, price and location of partial positive and significant influence on the variable intention to visit again. From the analysis of determination coefficient R Square value of variable product, promotion, price and location to give the effect of 72.1% against the interests of customers while the remaining 27.9% influenced by other factors not examined in this research.Keywords : Product , Promotion, Price, Location and Intention to visit again